Effectiveness of Risk Management on a Company’s Financial Performance: Study of Meta Analysis - Iswahyudi, Anggi Pradhita; Faisol, Faisol; Akbar, Muhammad; Wati, Sulaiha; Munawaroh, Siti (PT. Riset Press International, 2023)
This study aims to examine the effect of risk management on the company's financial performance. This study analyzes similar previous studies with the theme of risk management using a meta-analysis approach. The samples in this study were 20 previous studies in the form of journals or articles, consisting of 10 national journals and 10 international journals. The meta-analysis used in this study was effect size and data processing using Microsoft Excel and the JASP program (Jaffrey's Amazing Statistics Program). The results of this study indicate that risk management in any form greatly influences the company's financial performance, so it is very important for companies to implement risk management in order to minimize future company risk events.